Improved Predictability of Diagnosis and Prognosis Using Serum‐ and Tissue‐Derived Extracellular Vesicles From Bulk mRNA Sequencing in Pancreatic Ductal Adenocarcinoma - Qian Zhu; Zhang Chen; Ming Tian; Xin Yan; Xiangdong Gongye; Zhicheng Liu; Anbang Zhao; Zhiyong Yang; Yufeng Yuan (Cancer Medicine)
ABSTRACT Background Early‐stage pancreatic ductal adenocarcinoma (PDAC) is frequently misdiagnosed, contributing to its high mortality rate. Exosomal microRNAs (miRNAs) have emerged as potential biomarkers for the early detection of PDAC. Aims This study aimed to evaluate the feasibility of using exosomal miRNAs from PDAC tissues and serum as biomarkers for early detection and prognosis. Materials & Methods Exosomes were isolated from healthy individuals and PDAC patients via tissue and serum samples, then identified by analyzing their particle size and protein content. PDAC‐specific exosomal miRNAs were identified using a microRNA array. A large cohort was subsequently recruited to validate these findings. The diagnostic capacity of the identified miRNAs was assessed using the Brier score and area under the curve (AUC). Verified miRNAs were also used to confirm intracellular mRNA change patterns. Results The combination of miR142‐3p, miR148a‐3p, and CA199 showed a higher AUC (0.747) compared to CA199 alone (0.716) in ROC curve analysis. Gene Ontology (GO) annotations revealed that the two‐miRNA panel was associated with multiple oncogenic pathways. Discussion 142‐3p and miR148a‐3p were identified as specific to PDAC and, when combined with CA199, improved diagnostic accuracy. Their involvement in oncogenic pathways underscores their relevance as diagnostic and prognostic biomarkers. Conclusion MiR142‐3p and miR148a‐3p, alongside CA199, show promise as non‐invasive biomarkers for early detection and prognosis of PDAC, improving diagnostic accuracy.